The Risk Factors of HIV Incidence in Demak Regency in 2019 - Angraini, Ulfi; Cahyati, Widya Hary; Indriyanti, Dyah Rini (Public Health Perspective Journal, 2020)
HIV (Human Immunodeficiency Virus) is the virus that causes AIDS (Acquired Immuno Deficiency Syndrome) which attacks the human immune system and weakens the body's ability to fight any disease. One of the districts in Central Java, namely Demak Regency, is one of the areas that are quite high in HIV incidence and every year in that place has increased, therefore the aim of this study is to analyze the factors that influence the incidence of HIV in Demak Regency in 2019. This study used a cross sectional approach which was strengthened by interviews. The populations in this study were people who had tested HIV and were registered at the Demak District Health Office in 2019 and obtained 126 people. In this study, the sample was purposive sampling; with a total are 106 respondents. The instrument in this study was the provision of a questionnaire on sexual behavior, environment and socioeconomic status. After the data is obtained, it is analyzed by bivariate, univariate and multivariate. The results of this study indicate that there is a significant relationship between sexual behavior factors with a P-Value of 0.008, OR = 3.235 and a CI of 1.334 - 7.844. Besides that, socioeconomic status is also a risk factor associated with the HIV incidence with a P-Value of 0.001, OR = 0.253 and a CI of 0.111 - 0.575. Meanwhile, social environmental factors were not related to HIV incidence because the P-Value was 0.102, OR = 0.511 and CI was 0.227 - 1.149. However, the independent variable can only explain by the modelÃ‚Â  23.1% and there are other factors that influence the risk of HIV incidence.